Moral Injury and Spiritual Struggles in Military Veterans: A Latent Profile Analysis. Issue 3 (12th March 2019) - Currier, Joseph M.; Foster, Joshua D.; Isaak, Steven L.
Abstract: War‐related traumas can lead to emotional, relational, and spiritual suffering. Drawing on two community samples of war zone veterans from diverse military eras (Study 1, N = 616 and Study 2, N = 300), the purpose of this study was to examine patterns of constellations between outcomes related to moral injury (MI) and common ways in which veterans may struggle with religion or spirituality, defined as divine, morality, meaning, interpersonal, and doubt. Results from latent profile analyses revealed three distinct classes across the samples, based on psychometrically validated instruments: (a) no MI‐related outcomes or spiritual struggles ( nondistressed group; Study 1 = 72.7%, Study 2 = 75.0%); (b) MI‐related outcomes and equivalent or lower degrees of spiritual struggles relative to MI‐related outcomes ( psychological MI group; Study 1 = 19.2%, Study 2 = 17.0%); and (c) MI‐related outcomes and salient struggles with religious faith or spirituality, both within their own profiles and compared to other groups ( spiritual MI group; 8.1% and 8.0% in the two samples). When we compared severity of spiritual struggles within MI groups, turmoil with God or a higher power emerged as a defining feature of the spiritual MI group in both samples. In addition, secondary analyses revealed membership in this third group was linked with greater importance of religion or spirituality before military service, χ 2 (1, N = 616 and 300) = 4.468–8.273. Overall, although more research is needed, these findings highlight the possible utility of differentiating between psychological and spiritual subtypes of MI according to war zone veterans' religious or spiritual backgrounds. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Daño moral y luchas espirituales en veteranos de guerra: Un análisis de perfil latente DAÑO MORAL Y LUCHAS ESPIRITUALES Los traumas relacionados con la guerra pueden llevar al sufrimiento emocional, relacional, y espiritual. Basado en dos muestras comunitarias de veteranos de la zona de guerra de diversas épocas militares (Estudio 1, N = 616 y Estudio 2, N = 300), el objetivo de este estudio fue examinar los patrones de las constelaciones entre los resultados relacionados con el daño moral (DM) y las formas comunes en las que los veteranos pueden lidiar con la religión y/o la espiritualidad, definidas como divinas, moralidad, significado, interpersonal, y duda. Los resultados de los análisis de perfiles latentes revelaron tres clases distintas, basadas en instrumentos validados psicométricamente, en todas las muestras, aquellas con: (a) Los resultados no relacionados con el DM o luchas espirituales (grupo sin malestar psicológico, Estudio 1 = 72.7%, Estudio 2 = 75.0); (b) Los resultados relacionados con el DM y grados equivalentes o más bajos de luchas espirituales en relación con los resultados relacionados con el DM (grupo de DM psicológico ; Estudio 1 = 19.2%, Estudio 2 = 17.0); y (c) Los resultados relacionados con el DM y las luchas salientes con la fe religiosa y/o la espiritualidad, tanto dentro de sus propios perfiles como en comparación con otros grupos (grupo de DM espiritual ; 8.1 y 8.0% en las dos muestras). Cuando comparamos la severidad de las luchas espirituales dentro de los grupos DM, la confusión con Dios o un poder superior emergió como una característica definitoria del grupo espiritual DM en ambas muestras. Además, los análisis secundarios revelaron que la pertenencia a este tercer grupo se relacionaba con una mayor importancia de la religión y/o la espiritualidad antes del servicio militar, χ 2 (1, N = 616 y 300) = 4.468–8.273. En general, aunque se necesita más investigación, estos hallazgos resaltan la posible utilidad de diferenciar entre los subtipos psicológicos y espirituales de DM según los antecedentes religiosos y/o espirituales de los veteranos de la zona de guerra. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Moral Injury and Spiritual Struggles in Military Veterans: A Latent Profile Analysis Traditional Chinese 標題: 退役軍人的道德創傷與精神信仰困擾:潛在剖象分析 撮要: 戰爭相關的創傷可引致情緒、關係、精神方面的痛苦。本研究的兩組社區樣本由來自不同軍事時代、曾於戰區服役的退役軍人組成(研究 1, N = 616 及研究 2, N = 300)。本研究旨在檢視與道德創傷(MI)相關的症狀, 跟退役軍人受宗教和/或精神信仰的衝突所困的普遍情況之間的群集模式。我們把那些普遍困擾情況介定為神聖、道德、意義、人際關係和懷疑幾方面。潛在剖象分析基於已受驗證的心理測量工具, 在不同樣本中反映出3個不同類別:(a) 無MI相關症狀或精神信仰方面困擾(無悲痛組別; 研究 1 = 72.7%, 研究 2 = 75.0)、(b)有MI相關症狀並有與之同等或較低水平的精神信仰方面困擾(心理 MI 組別; 研究 1 = 19.2%, 研究 2 = 17.0)、(c) 無論在所屬組別剖象或與其他組別比較, 都有MI相關症狀, 並有顯著的宗教和/或精神信仰衝突(精神 MI 組別; 在兩組樣本中分別為 8.1 與 8.0%)。我們比較MI組別中的精神信仰困擾嚴重度時, 發現與神或更高存在的關係受擾是在兩組樣本中精神 MI 組別具定義性的特徵。再者, 次級分析反映, 屬於第三組別跟服役前宗教和/或精神信仰較重要有關(χ 2 (1, N = 616 與 300) = 4.468–8.273)。 雖然未來仍需有較多研究, 但總括來說, 是次研究發現凸顯, 根據退役軍人的宗教和/或精神信仰背景而區分出MI的心理和精神方面子類別可能有用。 Simplified Chinese 标题: 退役军人的道德创伤与精神信仰困扰:潜在剖象分析 撮要: 战争相关的创伤可引致情绪、关系、精神方面的痛苦。本研究的两组小区样本由来自不同军事时代、曾于战区服役的退役军人组成(研究 1, N = 616 及研究 2, N = 300)。本研究旨在检视与道德创伤(MI)相关的症状, 跟退役军人受宗教和/或精神信仰的冲突所困的普遍情况之间的群集模式。我们把那些普遍困扰情况介定为神圣、道德、意义、人际关系和怀疑几方面。潜在剖象分析基于已受验证的心理测量工具, 在不同样本中反映出3个不同类别:(a) 无MI相关症状或精神信仰方面困扰(无悲痛组别; 研究 1 = 72.7%, 研究 2 = 75.0)、(b)有MI相关症状并有与之同等或较低水平的精神信仰方面困扰(心理 MI 组别; 研究 1 = 19.2%, 研究 2 = 17.0)、(c) 无论在所属组别剖象或与其他组别比较, 都有MI相关症状, 并有显著的宗教和/或精神信仰冲突(精神 MI 组别; 在两组样本中分别为 8.1 与 8.0%)。我们比较MI组别中的精神信仰困扰严重度时, 发现与神或更高存在的关系受扰是在两组样本中精神 MI 组别具定义性的特征。再者, 次级分析反映, 属于第三组别跟服役前宗教和/或精神信仰较重要有关(χ 2 (1, N = 616 与 300) = 4.468–8.273)。 虽然未来仍需有较多研究, 但总括来说, 是次研究发现凸显, 根据退役军人的宗教和/或精神信仰背景而区分出MI的心理和精神方面子类别可能有用。